1973
DOI: 10.1139/g73-085
|View full text |Cite
|
Sign up to set email alerts
|

IRRADIATION OF SPERM AND OOCYTES INONCOPELTUS FASCIATUS(HEMIPTERA: LYGAEIDAE): SEX RATIO, FERTILITY, AND CHROMOSOME ABERRATIONS IN THE F1PROGENY

Abstract: Adult Oncopelfus fasciatus were irradiated as 7-to 8-day-old males, and as 3-to 4-or 10-to 12-day-old females with doses of 8 and 20 krad of gamma irradiation and 200 R of X-rays, respectively. Treated bugs were outcrossed to untreated bugs, and F, progeny derived from irradiated sperm and from prophase and metaphase oocytes were studied. All treated bugs were less fertile than the controls, but none of the treatments produced full sterility. Among the F, generation from the three types of crosses, there was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Males that transmit chromosome fragments have reduced fertility (LaChance et al, 1970). Chromosome fragments and translocations are correlated with arrested development and low fertility in Oncopeltus fasciatus (LaChance et al, 1970;LaChance and Richard, 1973). The drastic reduction of fertility of the progeny bearing fragmented and translocated chromosomal complements adds more evidence that inherited partial sterility observed in the Lepidoptera, which also possess holokinetic chromosomes, is based on the continued transmission of aberrant chromosomal complements (LaChance and Degrugillier, 1969).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Males that transmit chromosome fragments have reduced fertility (LaChance et al, 1970). Chromosome fragments and translocations are correlated with arrested development and low fertility in Oncopeltus fasciatus (LaChance et al, 1970;LaChance and Richard, 1973). The drastic reduction of fertility of the progeny bearing fragmented and translocated chromosomal complements adds more evidence that inherited partial sterility observed in the Lepidoptera, which also possess holokinetic chromosomes, is based on the continued transmission of aberrant chromosomal complements (LaChance and Degrugillier, 1969).…”
Section: Resultsmentioning
confidence: 99%
“…The drastic reduction of fertility of the progeny bearing fragmented and translocated chromosomal complements adds further evidence that inherited partial sterility observed is based on the continued transmission of aberrant chromosomal complements (La Chance and Degrugillier, 1969;La Chance et al, 1970). Lachance and Richard (1973) had reported that the O. fasciatus adults when irradiated with 8 and 20 Krad of gamma rays and 200 rad of X-rays, were less fertile than controls and none of the treated insects produced full sterility. The semi-sterility of the F1 males was correlated with chromosome translocation and fragmentation in the spermatocytes.…”
Section: Resultsmentioning
confidence: 99%
“…However, in both stages sex ratio alteration increased with a dose increase. Sex ratio distortion in Lepidoptera happened due to the chromosomal rearrangements which may disturb the mechanism that determines sex, perhaps by changing the production of hormones or enzymes that successively cause greater female/male mortality (Proshold &Bartell, 1970 andLa Chance &Richard, 1973) or as a consequence of recessive deadly mutations caused in the Z sex chromosomes (Marec et al, 1999).…”
Section: Pupal Stagementioning
confidence: 99%